2016
DOI: 10.1002/aoc.3637
|View full text |Cite
|
Sign up to set email alerts
|

Mild and efficient Pd(PtBu3)2‐catalyzed aminocarbonylation of aryl halides to aryl amides with high selectivity

Abstract: This work describes a mild and efficient approach for the synthesis of aryl amides via catalytic aminocarbonylation of aryl halides with alicyclic amines using a Pd (P t Bu 3 ) 2 /NH 4 Cl catalyst system. Under mild reaction temperature of 60°C and balloon pressure of CO, 5 mol% Pd(P t Bu 3 ) 2 with a cheap NH 4 Cl promoter is sufficient for high yields of aryl amides. The influence of reaction parameters such as reaction temperature, ligand type and promoter on catalytic activity was investigated. This work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Tu et al used a robust allyl Pd–NHC complex for the aminocarbonylation of aryl iodide with different amines under an atmospheric CO pressure and in the presence of base K 3 PO 4 (4 equiv) in toluene . Shi et al reported the aminocarbonylation of an aryl halide with amines in the presence of a Pd­(P t Bu 3 ) 2 catalyst, EtN­(i-Pr) 2 (1 equiv) as a base, and NH 4 Cl as a promoter in MeCN as the solvent . The optimal yield was obtained at 60 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Tu et al used a robust allyl Pd–NHC complex for the aminocarbonylation of aryl iodide with different amines under an atmospheric CO pressure and in the presence of base K 3 PO 4 (4 equiv) in toluene . Shi et al reported the aminocarbonylation of an aryl halide with amines in the presence of a Pd­(P t Bu 3 ) 2 catalyst, EtN­(i-Pr) 2 (1 equiv) as a base, and NH 4 Cl as a promoter in MeCN as the solvent . The optimal yield was obtained at 60 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Palladium catalyzed carbonylative coupling reactions of aryl halides with various nucleophiles represents a versatile method for the synthesis of aromatic carbonyl compounds, such as aromatic esters, amides, acids and ketones . Due to its inherent advantages, such as the readily available substrates, high functional group tolerance and good atom economy, this versatile method has become growing importance in organic synthesis …”
Section: Introductionmentioning
confidence: 99%
“…Carbonylative transformation of organic halides using palladium catalysts represents a versatile method for the synthesis of carboxylic acid and its derivatives [1][2][3][4]. Carbon monoxide, an inexpensive and readily available C 1 building block, is widely used as a carbonyl source for the palladium-catalyzed carbonylation of aryl halides [5][6][7][8][9][10][11][12]. However, except as a cheap carbonyl source, CO could also act as a strong π-acidic ligand for the palladium metal, thus resulting in a decrease of electron density for the palladium center and making the oxidative addition of aryl halide difficult [13,14].…”
Section: Introductionmentioning
confidence: 99%